Achieving outstanding damping performance through bio-inspired sutural tessellations. (September 2020) - Yu, Zhongliang; Liu, Junjie; Wei, Xiaoding
Highlights: We develop an analytical model to investigate the damping properties of sutural tessellations that are commonly found in many biological materials. Optimization of the damping performance of bio-inspired composites with sutural interfaces has been thoroughly discussed. Bio-inspired samples with sutural interfaces have been obtained through 3D printing and the dynamic experimental results validate our model predictions. Abstract: Architectured biological composites with sutural tessellations possess excellent static and dynamic mechanical properties. In this study, a dynamic analysis of the damping performance of composites with sutural interfaces is carried out based on the viscoelastic tension-shear model. Analytical formulae that connect the damping properties ( i.e., the loss modulus, storage modulus, and loss factor) of the composites with the morphology and the viscoelastic properties of constituents in triangular and trapezoidal sutures emerge from rigorous derivation. Further, our model points out that the appropriately designed sutural interfaces can enhance and optimize effectively the damping performance, which is validated by the dynamic mechanical analysis (DMA) tests on 3D printed samples. Finally, the effects of the sutural morphology and the viscoelastic properties of constituents on the optimization of the damping performance of the composites are systematically discussed. Our model suggests that the slant angles in the sutural tessellations in typical biological composites all have evolved to the optimal values to achieve the best damping performance.